The influence of crumb rubber on modified bitumen properties - Šernas, Ovidijus; Čygas, Donatas; Vaitkus, Audrius; Gumauskaitė, Vytautė (International Conference “Environmental Engineering”, 2017)
Rubber derived from grinding of recycled cars and trucks tyres may be successfully used as a bitumen modifier. Number of researches reported sufficient characteristics of rubber modified asphalt binders or modified asphalt mixes in terms of improved permanent deformation and fatigue cracking. The behavior of crumb rubber asphalt binders depends on several factors, such as modification method, rubber content and size, modification temperature, mixing speed and time applied during the digestion process. The aim of this study is to evaluate the effect of crumb rubber amount and type on modified bitumen low and high temperature properties. This paper presents results of unmodified bitumen, crumb rubber crumb rubber and polymer modified bitumen. Low and high temperature properties have been evaluated using bending beam rheometer and dynamic shear rheometer. Moreover, softening point and viscosity tests have been performed. The study results revealed that crumb rubber modified bitumen performed better than pure bitumen and similarly to polymer modified bitumen.
Keywords: crumb rubber; modified bitumen; rubber modified bitumen; permanent deformation; ow temperature performance